Relationships of Exclusion and Cohesion with Health: The Case of Bangladesh - Johnston, Heidi Bart (Journal of Health, Population and Nutrition, 2009)
The concept of social exclusion, applied widely in the European Union, has in recent years been gaining use in Bangladesh, mostly by international development agencies. Does this discourse of deprivation, developed in the welfare states of northern Europe, have salience in its application to deprivation in countries like Bangladesh where, for example, 31% of the rural population lives in chronic poverty? The concept of social exclusion has three principal components: a dynamic and relational perspective which requires the identification of who or what causes exclusion; an explicit recognition of multiple dimensions of deprivation; and a longitudinal perspective, recognizing that individuals and groups are dynamic intra- and intergenerationally. The Social Exclusion Knowledge Network of the World Health Organization Commission on Social Determinants of Health expanded the concept to include health status as a contributor to and an outcome of exclusion and to show that actors beyond the state or public sector can critically impact exclusionary processes. In the Bangladesh application, the relevance of the modified model was explored to find that while there are negative associations between social exclusion and health status, much stronger documentation is needed of the relationship. The modification of including multiple sectors, such as private enterprise and civil society, in addition to the state, as having potential to impact exclusionary processes is fundamental to the application of the social exclusion model in Bangladesh. Key words: Health equity; Social determinants of health; Social exclusion; Bangladesh doi: 10.3329/jhpn.v27i4.3387 J Health Popul Nutr 2009 Aug;27(4):426-440